Integrative synthesis of psychological support systems for enhancing athletic performance - Lykkeskov, M.; Askildsen, M. A.; Eckerdal, A. W. (Human Arenas, 2019)
Basic psychological science can make relevant contributions to sports. Through a pragmatic approach of the psychological support systems, ACT and CBT, and of Daniel Kahneman`s modes of thought, it is argued that a more holistic view on fitting psychological support systems to task needs is necessary in order to appropriately help athletes perform optimally. Such an integrated approach is arguably lacking. The holistic view is however noticeable in the way that chosen professional athletes already, no matter if this is through intentional practice or not, indicate integration of elements from not exclusively one psychological support system. So why should we limit ourselves, using only one when helping athletes? In extension of this, it is argued that a contextually unique synthesis of psychological support systems is needed, and that educated intuition, a guiding mechanism for actions, should be focused upon not only athletes but also coaches. Furthermore, this article should function as a catalyst to initiate such an implementation, to a practical setting.